Development experience and emerging challenges : Bangladesh - Shahabuddin, Quazi; Rahman, Rushidan Islam; Bangladesh Institute of Development Studies (Dhaka : University Press, 2009)
Contributed papers presented at an international conference organized by Bangladesh Institute of Development Studies in December 2007.
"Bangladesh Institute of Development Studies."
Includes bibliographical references.
Donated By Akbar Ali Khan
Keywords: Bangladesh -- Economic conditions -- Congresses; Bangladesh -- Economic policy -- Congresses